ENGLISH LANGUAGE EDUCATION PROGRAM SECOND-YEAR STUDENTS’ SPEAKING DIFFICULTIES IN AN ACADEMIC SPEAKING CLASS - Satya Monique Saragih; Listyani - Listyani (English Language Education Department, Universitas Kristen Duta Wacana (UKDW), Yogyakarta, Indonesia, 2021)
Academic Speaking class is the last speaking class that students at an English Language Education Program (ELEP) have to take. However, to pass this class is not very easy because the students had to be able to speak in an academic context. Seeing this phenomenon, the researchers tried to identify the second-year students’ difficulties in the Academic Speaking class, in a private university in Central Java. There are three research questions in this research, “What are ELEP second-year students’ speaking difficulties in Academic Speaking class?”, “What factors contribute to the speaking difficulties in Academic Speaking class?’, and What strategies do the Academic Speaking students employ to overcome the difficulties?”. This research used both qualitative and quantitative approaches that took place at an ELEP and involved 38 participants from three Academic Speaking classes. The data were taken using questionnaires and interviews. This study acknowledged 8 difficulties in speaking English, difficulties in dealing with anxiety, over-using mother tongue, giving a spontaneous response, learning unfamiliar and strange accents, expressing ideas, finding the right lexicon, ordering the right grammatical patterns, and dealing with a competitive environment. Subsequently, the factors which contributed to the difficulties were students’ lack of confidence and lack of vocabulary. The findings of the study are hoped to be advantageous for both students and teachers in the Academic Speaking class.